GROWTH PERFORMANCE OF SORGHUM (SORGHUM BICOLOR L.) AS INFLUENCED BY LEGUMES INCORPORATION AND NITROGEN APPLICATION IN SUDAN SAVANNA OF NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Soil fertility improvement creates the environment for plant to optimally express itself in growth and development, and subsequently higher yield. The study was set up to determine the influence of incorporated legumes and nitrogen on growth and development of sorghum (Sorghum bicolor L.). Field experiments were carried out in the wet seasons of 2015 and 2016 at the Research Farm of Federal University Dutsin-Ma, Nigeria, The treatments consisted of four levels of N (0, 30, 60 and 90kg N ha -1), and four legumes (Lablab (Lablab purpureus), Mucuna (Mucuna pruriens), Soybean (Glycine max L. Merrill), and Cowpea (Vigna unguiculata L.)) and no legume. SAMSORG 40 variety was used in this experiment. The experiment was laid out in a randomized complete block design and replicated three times. Nitrogen application significantly (P
Keywords: Incorporation, Legume, Nitrogen, Sorghum. Growth